“Conversion surgery” for locally advanced pancreatic cancer: a position paper by the study group at the joint meeting of the International Association of Pancreatology (IAP) & Japan Pancreas Society (JPS) 2022 - Oba, Atsushi; Del Chiaro, Marco; Fujii, Tsutomu; Okano, Keiichi; Stoop, Thomas F.; Wu, Y. H. Andrew; Maekawa, Aya; Yoshida, Yuta; Hashimoto, Daisuke; Sugawara, Toshitaka; Inoue, Yosuke; Tanabe, Minoru; et al. (Pancreatology, 2023)
Locally advanced pancreatic cancer (LAPC), which progresses locally and surrounds major vessels, has historically been deemed unresectable. Surgery alone failed to provide curative resection and improve overall survival. With the advancements in treatment, reports have shown favorable results in LAPC after undergoing successful chemotherapy therapy or chemoradiation therapy followed by surgical resection, so-called “conversion surgery”, at experienced high-volume centers. However, recognizing significant regional and institutional disparities in the management of LAPC, an international consensus meeting on conversion surgery for LAPC was held during the Joint Congress of the 26th Meeting of the International Association of Pancreatology (IAP) and the 53rd Annual Meeting of Japan Pancreas Society (JPS) in Kyoto in July 2022. During the meeting, presenters reported the current best multidisciplinary practices for LAPC, including preoperative modalities, best systemic treatment regimens and durations, procedures of conversion surgery with or without vascular resections, biomarkers, and genetic studies. It was unanimously agreed among the experts in this meeting that “cancer biology is surpassing locoregional anatomical resectability” in the era of effective multiagent treatment. The biology of pancreatic cancer has yet to be further elucidated, and we believe it is essential to improve the treatment outcomes of LAPC patients through continued efforts from each institution and more international collaboration. This article summarizes the agreement during the discussion amongst the experts in the meeting. We hope that this will serve as a foundation for future international collaboration and recommendations for future guidelines.
Online verfügbar: 7. Juni 2023, Artikelversion: 7. September 2023
Gesehen am 15.11.2023